ASUPAN LEMAK, AKTIVITAS FISIK DAN KEGEMUKAN PADA REMAJA PUTRI DI SMP BINA INSANI SURABAYA[Fat Intake, Physical Activity and Obesity among Adolescent Girls in SMP Bina Insani Surabaya] - Jayanti Ayu Praditasari; Sri Sumarmik (Media Gizi Indonesia, 2018)
Obesity is defi ned as excessive fat accumulation fat that causes excess weight. Diseases that related with obesity are diabetes, dyslipidemia, hypertension and other degenerative diseases. Factors that affect obesity are dietary factors, history of hereditary, lifestyle, psychological factors, environment, individual, and biological which may infl uence energy intake and expenditure. Consumption of high fat in a long period without any activity for energy expenditure can increase the risk of obesity. This study was aimed to analyse the correlation between fat intake and physical activity with obesity among adolescent girls in SMP Bina Insani junior high school Surabaya. This study employed a case control study design with a retrospective approach. The research participants were 32 female students in Bina Insani junior high school Surabaya (16 control and 16 case samples). Total fat intake was relatively low. The intake of Monounsaturated Fatty Acids (MUFA) and Polyunsaturated Fatty Acids (PUFA) were low while Saturated Fatty Acids (SFA) were high. There was no correlation between fat intake and obesity (ρ=0.240), but there was a signifi cant correlation between physical activity ρ=0.006 (OR= 9.533, 95% CI: 1.847-49.204) with adolescent obesity. The very mild physical activity give a risk as much as 9.533 times greater for developing obesity than the mild physical. Therefore, it is necessary to increase physical activity among adolescent girls by doing sports to reduce the risk of obesity.